Osobennosti tekhnicheskoi podgotovlennosti rossiiskikh gandbolistok-vratarei - Ignateva, V. J.; Petrachyova, I. V.; Gusev, A. V. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The purpose of this research was to examine the technical preparedness of elite female handball goalkeepers. The authors compared the technique of the Russian superleague goalkeepers and the technique of players of national teams on the world championship. Eight basic ways apply to the detention of a ball by main goalkeepers of the world and the Russian superleague goalkeepers. The quantity of ways of the detention of a ball used in game by the players of that class considerably does not differ. The analysis of ways of the detention of a ball in the game of various qualification players has revealed the significant distinction in the "school" of a game, and not for the benefit of the Russian foremen.